A microfabricated ion trap with integrated microwave circuitry - Allcock, D; Harty, T; Ballance, C; Keitch, B; Linke, N; Stacey, D; Lucas, D (American Institute of Physics, 2012)
We describe the design, fabrication and testing of a surface-electrode ion trap, which incorporates microwave waveguides, resonators and coupling elements for the manipulation of trapped ion qubits using near-field microwaves. The trap is optimised to give a large microwave field gradient to allow state-dependent manipulation of the ions' motional degrees of freedom, the key to multiqubit entanglement. The microwave field near the centre of the trap is characterised by driving hyperfine transitions in a single laser-cooled 43Ca+ ion.